2018
DOI: 10.1002/eat.22861
|View full text |Cite
|
Sign up to set email alerts
|

The impact of weight suppression and weight loss speed on baseline clinical characteristics and response to treatment

Abstract: In our study, both WS and WLS were associated with baseline "core" clinical variables and provided complementary abilities to predict weight gain and remission at the end of treatment. If replicated, our data suggest the importance of considering both WS and WLS as useful clinical variables in the baseline assessment of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…However, as all patients had regained to a minimally normal weight, they were undoubtedly less weight‐suppressed than prior to admission to acute treatment, and it is possible that a greater degree of WS would have manifested an effect on clinical outcome. On the other hand, the mean WS of our group was similar to that of several other studies which found a significant relationship between WS and eating disorder symptoms (Burnette, Simpson, & Mazzeo, 2017, 2018; Solmi et al, 2018). We examined the definition of WS used by most prior studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, as all patients had regained to a minimally normal weight, they were undoubtedly less weight‐suppressed than prior to admission to acute treatment, and it is possible that a greater degree of WS would have manifested an effect on clinical outcome. On the other hand, the mean WS of our group was similar to that of several other studies which found a significant relationship between WS and eating disorder symptoms (Burnette, Simpson, & Mazzeo, 2017, 2018; Solmi et al, 2018). We examined the definition of WS used by most prior studies.…”
Section: Discussionsupporting
confidence: 91%
“…While several studies have found that WS and/or its interaction with BMI predict change in weight during treatment (Berner et al, 2013; Carter et al, 2015; Piers et al, 2019; Wildes & Marcus, 2012), WS has not been shown to consistently relate to other indices of treatment outcome, such as likelihood of drop‐out (Solmi et al, 2018; Wildes & Marcus, 2012), achieving weight restoration (Witt et al, 2014), duration of illness (Witt et al, 2014), or illness remission (Solmi et al, 2018). To our knowledge, only one other study to date has examined the influence of WS on weight trajectory following treatment in AN (Bodell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reorganization of the brain network showed significant relationships with BMI and reduced volumes of gray matter, as an association was evident between differences in topological properties and differences in cortical volumes, particularly in the parietal cortex where lower levels of clusterization and efficiency were observed in the most affected areas. Further studies could be useful to evaluate the impact of weight loss as well as weight loss speed on brain network architecture (Solmi et al, 2018). Moreover, longitudinal evaluations are needed to better understand how much all these alterations are a consequence of malnutrition and how much weight gain is associated with a recovery of network brain organization.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first study that included patients at different AN stages of their disorder to investigate a possible role of disorder duration in determining hippocampal alterations and providing evidence that a reduced hippocampal volume is not to be considered an index of neuroprogression in AN (Treasure et al, 2015), since it is present from the very first stages of the disorder. Furthermore, the correlation between whole hippocampal volume and BMI is a particularly interesting finding because it helps in clarifying the possible causal role of malnutrition in the structural alteration of this brain area, although the role of weight suppression and speed of weight loss on brain atrophy remains to be understood and explored (Solmi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%